PROFIL KLINIS PASIEN DENGAN KOINFEKSI HIV DAN TB DI RSUD DR. SOETOMO PERIODE JANUARI 2021-DESEMBER 2022 - Rafif Razan Abdillah; Rebekah Juniati Setiabudi; Musofa Rusli; Vitanata Arfijanto (Journal of Innovation Research and Knowledge, 2026)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis, is one of the most common opportunistic infections and a leading cause of mortality among people living with Human Immunodeficiency Virus (HIV). TB infection accelerates the progression of HIV to Acquired Immunodeficiency Syndrome (AIDS), making early identification and appropriate management essential. This study aimed to describe the clinical profile of patients with HIV-TB coinfection treated at Dr. Soetomo Regional General Hospital, Surabaya, a national referral hospital, during January 2021–December 2022. Methods: This descriptive study employed a retrospective design using secondary medical record data. Samples were selected through consecutive sampling based on predetermined inclusion and exclusion criteria. Data were analyzed descriptively to characterize the demographic and clinical profiles of patients with HIV-TB coinfection. Results: A total of 34 patients met the study criteria. Most patients were aged 26–45 years (47.1%), male (71%), employed in the private sector (38.2%), and had completed senior high school education (58.3%). The majority developed TB within one year after being diagnosed with HIV (55.9%). The most frequently prescribed antiretroviral (ARV) regimen was Tenofovir (TDF) + Lamivudine (3TC) + Efavirenz (EFV) (58.8%). Conclusion: HIV-TB coinfection at Dr. Soetomo Regional General Hospital predominantly occurred within the first year following HIV diagnosis. The TDF+3TC+EFV regimen was the most commonly administered ARV treatment. These findings provide useful baseline information for improving early detection, clinical monitoring, and management strategies for patients with HIV-TB coinfection.